Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter P - Section P.6 - Rational Expressions - Exercise Set - Page 85: 56


$-\displaystyle \frac{(x+3)(x-1)}{(x+2)(x-2)},\qquad x\neq 2, -2$

Work Step by Step

Factor each denominator. $x^{2}-4=(x+2)(x-2)\qquad $... (a difference of squares) $LCD=(x+2)(x-2)$ $\displaystyle \frac{x+5}{x^{2}-4}-\frac{x+1}{x-2}=\frac{x+5}{(x+2)(x-2)}-\frac{x+1}{x-2}$ $=\displaystyle \frac{x+5}{(x+2)(x-2)}-\frac{x+1}{x-2}\times\frac{x+2}{x+2}$ $=\displaystyle \frac{x+5}{(x+2)(x-2)}-\frac{x^{2}+3x+2}{(x+2)(x-2)}$ $=\displaystyle \frac{x+5-x^{2}-3x-2}{(x+2)(x-2)}$ $=\displaystyle \frac{-x^{2}-2x+3}{(x+2)(x-2)}$ $=\displaystyle \frac{-(x^{2}+2x-3)}{(x+2)(x-2)}$ ... two factors of -3 with sum +2 are $+3$ and $-1$ $=-\displaystyle \frac{(x+3)(x-1)}{(x+2)(x-2)},\qquad x\neq 2, -2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.